Pengaruh pendidikan kesehatan terhadap pengetahuan dan keterampilan pertolongan pertama cedera olahraga dengan metode prices pada anggota futsal - Evi Triyani; Meida Laely Ramdani (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This research aimed to discover the effect of health education on the knowledge and skills of sports injuries first aid using the PRICES method. Methods:  This was pre-experimental quantitative research with one group pre-test-post-test design approach. There were 27 members of a futsal group taken as the research sample using an accidental sampling technique. The data obtained were analyzed using the paired t-test. Results:  The lowest and the highest score of the respondents' knowledge before the health education was given were 4 and 13 respectively. While after the health education was given, the lowest score was 7 and the highest one was 15. The lowest and the highest score of the respondents' skills before the simulation were 25 and 68 respectively. While after the simulation, the lowest and the highest score were 75 and 93 respectively. Based on the t-test result, p-value of knowledge and skills was 0,000 (p 0.05). H0 is rejected if p is 0.05. It means that there were differences before and after the health education was given. Conclusion:  There was an effect of health education on the knowledge and skills of sports injuries first aid with the PRICES method on futsal members.